A Novel Transcriptional Factor Important for Pathogenesis and Ascosporogenesis in Fusarium graminearum - Yang Wang; Wende Liu; Zhanming Hou; Chenfang Wang; Xiaoying Zhou; Wilfried Jonkers; Shengli Ding; H. Corby Kistler; Jin-Rong Xu (Molecular Plant-Microbe Interactions, 2011)
Fusarium head blight or scab caused by Fusarium graminearum is an important disease of wheat and barley. The pathogen not only causes severe yield losses but also contaminates infested grains with mycotoxins. In a previous study, we identified several pathogenicity mutants by random insertional mutagenesis. One of these mutants was disrupted in the ZIF1 gene, which encodes a b-ZIP transcription factor unique to filamentous ascomycetes. The Δzif1 mutant generated by gene replacement was significantly reduced in deoxynivalenol (DON) production and virulence on flowering wheat heads. It was defective in spreading from inoculated florets to the rachis and other spikelets. Deletion of the ZIF1 ortholog MoZIF1 in the rice blast fungus also caused reductions in virulence and in invasive growth. In addition, the Δzif1 mutant is defective in sexual reproduction. Although it had normal male fertility, when selfed or mated as the female in outcrosess, the Δzif1 mutant produced small, pigmented perithecia that were sterile (lack of asci and ascospores), suggesting a female-specific role for ZIF1 during fertilization or ascus development. Similar female-specific defects in sexual reproduction were observed in the ΔMozif1 mutant. When mated as the female, the ΔMozif1 perithecia failed to develop long necks and asci or ascospores. The ZIF1 gene is well conserved in filamentous ascomycetes, particularly in the b-ZIP domain, which is essential for its function. Expression of ZIF1 in Magnaporthe oryzae complemented the defects of the ΔMozif1 mutant. These results indicate that this b-ZIP transcription factor is functionally conserved in these two fungal pathogens for plant infection and sexual reproduction.